2010
DOI: 10.1111/j.1872-034x.2010.00670.x
|View full text |Cite
|
Sign up to set email alerts
|

Crucial role of impaired Kupffer cell phagocytosis on the decreased Sonazoid‐enhanced echogenicity in a liver of a nonalchoholic steatohepatitis rat model

Abstract: CEUS with Sonazoid is a powerful evaluation tool to diagnose NASH from an early stage of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…Although multiple factors could affect WR, reduced Kupffer cell phagocytic function may be one of the most conceivable reasons. It was reported that nonalcoholic steatohepatitis in a rat model showed reduced Kupffer cell phagocytic function, with no changes in the numbers of Kupffer cells [24]. More recently, Park et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although multiple factors could affect WR, reduced Kupffer cell phagocytic function may be one of the most conceivable reasons. It was reported that nonalcoholic steatohepatitis in a rat model showed reduced Kupffer cell phagocytic function, with no changes in the numbers of Kupffer cells [24]. More recently, Park et al.…”
Section: Discussionmentioning
confidence: 99%
“…If the Kupffer cells phagocytose more contrast agent, less contrast agent can flow into the HV, and the PV‐HV AT interval can be prolonged. However, the influence on the AT interval might be relatively small because it would take more time for Kupffer cells to phagocytose contrast agents …”
Section: Discussionmentioning
confidence: 99%
“…The postvascular phase was observed using the advanced dynamic flow (ADF) mode in some cases. Using the ADF mode, Sonazoid bubbles phagocytosed by Kupffer cells were destroyed, with a high MI of 1.0 [5]. Since the presence or absence of hypoechoic areas in the postvascular phase cannot be readily identified, particularly in high-echoic lesions, this procedure is useful for such determination.…”
Section: Methodsmentioning
confidence: 99%
“…All procedures followed were in accordance with the ethical standards of the responsible committee on human experimentation (institutional and national) and with the Helsinki Declaration of 1975, as revised in 2008 [5]. Informed consent was obtained from all patients for being included in the study.…”
Section: Consentmentioning
confidence: 99%